Spin-Crossover Complexes - Kazuyuki Takahashi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The spin-crossover (SCO) phenomenon originates from the intrinsic bistability of the d-electron configuration, created by the competition between ligand-field splitting and spin-pairing energies in a first coordination sphere of transition metal ions. Since Cambi's visionary finding of the SCO phenomenon in 1931, considerable knowledge concerning syntheses, crystal structures, magnetic and thermodynamic properties, spectroscopies, molecular orbital calculations, and theories of SCO complexes has accumulated in a very large number of inorganic molecular coordination compounds, and, in addition, inorganic cobaltates and bioinorganic molecular systems. Recent studies which have focused on other electronic properties exhibited by SCO complexes themselves, control of molecular assemblies, and moreover, multifunctionalization of SCO complexes with either different electronic properties or porous frameworks will open the possibility toward future practical applications of SCO complexes. Thus, the fundamentals and applications of SCO complexes afford a very exciting research field in inorganic coordination chemistry and continues to attract growing attention on a wide range of relevant research fields. This Special Issue aims at collecting research and review contributions concerning recent advances in all aspects of SCO and related phenomena and disseminating this extensive knowledge with a broader audience by means of open access publishing. I invite you to contribute papers in the following research areas so that your research can impact the next generation trends in this promising field.